PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KETERAMPILAN BERBAHASA di SMPN 14 KOTA SERANG - Sukreni; Joko Widodo; Ajang Budiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has transformed patterns of communication in society, particularly among adolescents. One significant change is in language use, which is now heavily influenced by social media. This study aims to describe the influence of social media usage on students’ language skills, especially writing and reading skills, at SMPN 14 Serang City. The theoretical framework of this study is based on Stephen Krashen’s Second Language Acquisition theory, which emphasizes the importance of comprehensible input and a supportive learning environment in language acquisition. This research is also strengthened by digital linguistic theories that explain how social media shapes communication patterns and language styles among younger generations. This study employs a quantitative approach using a descriptive correlational method. The research population consists of ninth-grade students at SMPN 14 Serang City, with a sample of 78 students selected through stratified random sampling. The instruments used include a questionnaire measuring the intensity of social media use as well as reading and writing tests. Data were analyzed using Pearson correlation and simple linear regression. The results indicate that most students at SMPN 14 Serang City have good writing and reading abilities. Writing activities on social media, such as creating status updates, captions, private messages, and comments, indirectly train students to construct sentences and express ideas. Students’ reading abilities are also supported by exposure to various texts on social media, although deeper comprehension still needs improvement. The correlation test shows a positive and significant relationship between the intensity of social media use and writing skills (r = 0.45; p < 0.05) as well as reading skills (r = 0.38; p < 0.05). These findings indicate that social media use contributes to the development of students’ literacy skills, particularly in writing fluency and literal reading comprehension, although guidance is still needed to ensure appropriate and standard language use.